A Research and Development Study on Interactive Learning Media for Students with Special Needs in Inclusive Elementary Schools - Sucipto; Moh. Mahfud Effendi; Yuni Pantiwati (Universitas Pendidikan Ganesha, 2026)
The problem in this study is the limited use of interactive learning media for students with special needs (ABK), resulting in learning being still dominated by conventional media that are less suitable for their learning characteristics. This condition leads to low levels of interest, engagement, and understanding among students, especially in abstract topics such as the Solar System. This study aims to develop and test the feasibility of interactive learning media for students with special needs on the Solar System topic in inclusive elementary schools. This research uses the Research and Development (R&D) method with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. Data were collected through observation, interviews, expert validation questionnaires (covering content, language, media, and special education aspects), and product trials. Data analysis was conducted using descriptive quantitative methods with feasibility percentages. The results show that the developed media is categorized as highly feasible based on expert validation scores ranging from 78.13% to 100%, and received very good responses in both small and large group trials with achievement levels of 90% to 98%. The conclusion of this study indicates that the developed interactive learning media is valid, practical, and effective for students with special needs because it can improve students’ interest, engagement, and learning comprehension. The implication is that this media serves as an innovative alternative for teachers in creating more adaptive and inclusive learning that is in accordance with the needs of students with special needs.